Neuropeptide manipulation has behavioural and cascading fitness consequences in wild-living fish. (November 2019) - Stiver, Kelly A.; Marsh-Rollo, Susan E.; Alonzo, Suzanne H.
Abstract : Due to the difficulty of simultaneously assessing variation in individual physiology, behaviour and fitness, we often know little about the mechanistic basis of life-history trade-offs and fitness variation. It is similarly challenging to examine how physiological variation in one individual has cascading fitness consequences for others in the social environment. Using a wild-living fish (ocellated wrasse, Symphodus ocellatus ), we manipulated a neuropeptide pathway associated with courtship, aggression and parental care in vertebrates (arginine vasotocin, AVT) and directly examined the behavioural and fitness consequences. Nesting males injected with the AVT antagonist increased their paternal care, resulting in increased hatching of offspring and increased reproductive success of all individuals that mated at his nest. By directly examining physiology, behaviour and reproductive success, we revealed how a small change in individual physiology has clear and direct fitness consequences for multiple individuals. Highlights: We examined physiology, behaviour and reproductive success in ocellated wrasse. We injected nesting males with arginine vasotocin (AVT), an AVT blocker, or saline. Males injected with AVT blocker provided more care and had higher fitness.